Online music stores: A modern approach in enticing consumers in buying music albums - Arceleta,Patricia Bianca C. Balbin,John Robert S. Del Rosario,Macy Anne F. Mabido,Grazelle N. and Sace, Kristina Lailyn S. 4 0 16; 5 (2016)
u
Business Research: (BSBA major in Marketing Masnagement) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2